Respostas

2014-02-17T07:46:30-03:00
         2x (x+3) = x² + 3x + 70

 2x .x  + 2x .3 = x² + 3x + 70

2x² + 6x =  x² + 3x + 70

2x² - x² + 6x - 3x - 70 = 0

x² + 3x - 70 =0  ( agora só encontrar as raízes )

a = 1
b = 3
c = - 70

Δ= b² - 4.a.c  ~> Δ = 3² - 4.1.(-70) = 289

x1 = -b + √Δ / 2.a

x1 = -3 + √ 289 / 2.1  ~> 7

x2 = -b - √Δ /2a
 

x2 = - 3 - √ 289 / 2  ~>   \frac{-20}{2} = - 10

Solução : { 7  , - 10 }

1 5 1
Comentário foi eliminado
Comentário foi eliminado
Comentário foi eliminado
Comentário foi eliminado
Comentário foi eliminado